Photoreceptor engineering - Ziegler, Thea; Möglich, Andreas (Frontiers in Molecular Biosciences, 2015)
Sensory photoreceptors not only control diverse adaptive responses in Nature, but as light-regulated actuators they also provide the foundation for optogenetics, the non-invasive and spatiotemporally precise manipulation of cellular events by light. Novel photoreceptors have been engineered that establish control by light over manifold biological processes previously inaccessible to optogenetic intervention. Recently, photoreceptor engineering has witnessed a rapid development, and light-regulated actuators for the perturbation of a plethora of cellular events are now available. Here, we review fundamental principles of photoreceptors and light-regulated allostery. Photoreceptors dichotomize into associating receptors that alter their oligomeric state as part of light-regulated allostery and non-associating receptors that do not. A survey of engineered photoreceptors pinpoints light-regulated association reactions and order-disorder transitions as particularly powerful and versatile design principles. Photochromic photoreceptors that are bidirectionally toggled by two light colors augur enhanced spatiotemporal resolution and use as photoactivatable fluorophores. By identifying desirable traits in engineered photoreceptors, we provide pointers for the design of future, light-regulated actuators.